A Robust Recovery of Ni From Laterite Ore Promoted by Sodium Thiosulfate Through Hydrogen-Thermal Reduction - Liu, Shoujun; Yang, Chao; Yang, Song; Yu, Zhongliang; Wang, Zhao; Yan, Kang; Li, Jin; Liu, Xingyang (Frontiers in Chemistry, 2021)
Laterite ore is one of the important sources of nickel (Ni). However, it is difficult to liberate Ni from ore structure during reduction roasting. This paper provided an effective way for a robust recovery of Ni from laterite ore by H2 reduction using sodium thiosulfate (Na2S2O3) as a promoter. . It was found that a Ni content of 9.97% and a Ni recovery of 99.24% were achieved with 20 wt.% Na2S2O3 at 1100 oC. The promoting mechanism of Na2S2O3 in laterite ore reduction by H2 was also investigated. The thermogravimetric results suggested the formation of Na2Mg2SiO7, Na2SO3, Na2SO4, and S during the pyrolysis of laterite with Na2S2O3, among which the alkali metal salts could destroy the structures of nickel-bearing silicate minerals and hence release Ni, while S could participate in the formation of the low-melting-point eutectic phase of FeS-Fe. The formation of low-melting-point phases were further verified by the morphology analysis, which could improve the aggregation of Ni-Fe particles due to the capillary forces of FeS-Fe as well as the enhanced element migration by the liquid phase of sodium silicates during reduction.